ANALISIS PERAN KOMITE SEKOLAH SEBAGAI MITRA STRATEGIS DALAM PENINGKATAN MUTU PENDIDIKAN - Wiwik Dyah Aryani; Ai Yunita; Romlah Rosmawati; Neneng Dian Handayani; Kiki Yuwantika (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the role of school committees as strategic partners in improving educational quality at SDN 151 Sukasenang and SDN 229 Cibaduyut, Bandung City. The research employed a qualitative descriptive approach involving 13 participants, consisting of principals, teachers, school committee members, and parents. Data were collected through interviews, observations, and documentation, then analyzed using data reduction, data display, and conclusion drawing techniques. The findings reveal that school committees have performed their functions as advisory, supporting, controlling, and mediating agencies. Effective communication, commitment, and collaboration support their role, while limited participation and resources remain significant challenges in educational improvement efforts.